State-owned Enterprises as Institutional Market Actors in the Marketization of Public Service Provision: A Comparative Case Study of Danish and Swedish Passenger Rail 1990–2015 - Lene Tolstrup Christensen (Copenhagen Business School (CBS), 2016)
This doctoral thesis (PhD) explores from a public governance perspective the role of stateowned enterprises (SOEs) in an era of marketization of public service provision and thus contributes to the renewed academic interest in contemporary SOEs. It builds on an explorative comparative case study of DSB SOV and SJ AB in the marketization of passenger rail in Denmark and Sweden respectively from the 1990s to 2015. In the period both cases kept full state ownership and Sweden gradually exposed all services to competition whereas in Denmark with time competition was put on hold. The case study consists of document study and +50 interviews and is based on a historical institutionalist perspective on gradual change that emphasizes interpretation in the implementation between rule makers and rule takers as a driver of institutional change. It leads to the conceptualization of the SOE as an institutional market actor (IMA).
hdl:10398/9410
Keywords: 650